Public Service Transformation Can Change Fishermen's Community Thinking and Behavior on Regency Buton - Didi, La (Ilomata International Journal of Social Science, 2024)
This transformation is carried out using three approaches: support, capacity and value or benefits of the Gitar Kombena application. These approaches are closely related to the change of mindset and behaviour in the public sector service. The transformation aims to improve the efficiency and efficiency of public services as well as provide ease of access, transparency, and accountability to the needs of the public. This research uses descriptive methods. Researchers collect data through interviews, observations, and documentation. Data collected is analyzed from the collection stage, data condensation, data verification and conclusion. Research results show that the transformation is supported by government and infrastructure, but limited to finance, and public knowledge in the use of digital services. As for the capacity of human resources bureaucracy contributes to improving the quality of public services, while the benefits of using the application Gitar Kombena has promoted services that are effective, efficient, accountable, transparent and successfully changing the mindset and behavior of the public as well as bureaucracies in the public service. Further research is needed on the impact of transformation on the economy of the fishing community.